Safety and efficacy of long‐term emicizumab prophylaxis in hemophilia A with factor VIII inhibitors: A phase 3b, multicenter, single‐arm study (STASEY). Issue 8 (14th November 2022) - Jiménez‐Yuste, Víctor; Peyvandi, Flora; Klamroth, Robert; Castaman, Giancarlo; Shanmukhaiah, Chandrakala; Rangarajan, Savita; García Chavez, Jaime; Martinez, Raul; Kenet, Gili; Alzahrani, Hazaa; Robson, Susan; Schmitt, Christophe; et al.
Abstract: Background: The bispecific monoclonal antibody emicizumab bridges activated factor IX and factor X, mimicking the cofactor function of activated factor VIII (FVIII), restoring hemostasis. Objectives: The Phase 3b STASEY study was designed to assess the safety of emicizumab prophylaxis in people with hemophilia A (HA) with FVIII inhibitors. Methods: People with HA received 3 mg/kg emicizumab once weekly (QW) for 4 weeks followed by 1.5 mg/kg QW for 2 years. The primary objective was the safety of emicizumab prophylaxis, including incidence and severity of adverse events (AEs) and AEs of special interest (thrombotic events [TEs] and thrombotic microangiopathies). Secondary objectives included efficacy (annualized bleed rates [ABRs]). Results: Overall, 195 participants were enrolled; 193 received emicizumab. The median (range) duration of exposure was 103.1 (1.1–108.3) weeks. Seven (3.6%) participants discontinued emicizumab. The most common AEs were arthralgia ( n = 33, 17.1%) and nasopharyngitis ( n = 30, 15.5%). The most common treatment‐related AE was injection‐site reaction ( n = 19, 9.8%). Two fatalities were reported (polytrauma with fatal head injuries and abdominal compartment syndrome); both were deemed unrelated to emicizumab by study investigators. Two TEs occurred (myocardial infarction and localized clot following tooth extraction), also deemed unrelated to emicizumab. The negative binomial regression model–based ABR (95% confidence interval) for treated bleeds was 0.5 (0.27–0.89). Overall, 161 participants (82.6%) had zero treated bleeds. Conclusions: The safety profile of emicizumab prophylaxis was confirmed in a large population of people with HA with FVIII inhibitors and no new safety signals occurred. The majority of participants had zero treated bleeds.